Focused ion beam nanomachining for analyzing effects of light-structure interaction on hair color - Wang, Houxiao (2015)
The light-structure interaction was considered for hair color deciphering. Using focused ion beam (FIB) nanomachining and scanning electron microscopy (SEM) imaging, the hair shaft structures were observed, and the effects of light-structure interaction on hair coloration/whitening were analyzed. It was shown that the outer structural morphologies of the cuticles for both black and white hair shafts were nearly the same (like the stepped and discontinuous antireflection surface relief gratings), and a highly-packed melanin layer, which could make the black hair act like a 'black body' to fully absorb incident photons, clearly located in the joint region between the cortex and the cuticle of the black hair, however, no such melanin layer was found in the white hair shaft. Moreover, the lack of pigments during hair whitening resulted in obvious changes of the inner hair structure, i.e., the melanin granules in the black hair were not observed in the white hair leading to a porous structure consisting of lots of nanoscale hollow spaces, and these nanoholes could act like the nanoscopic mirrors to reflect the incident white light, contributing to the color alteration in the human hair shafts.